2023
DOI: 10.3390/biomimetics8010072
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stents: Technical and Clinical Progress

Abstract: Drug-eluting stents (DES) demonstrated superior efficacy when compared to bare metal stents and plain-old balloon angioplasty and are nowadays used in almost all percutaneous revascularization procedures. The design of the stent platforms is constantly improving to maximize its efficacy and safety. Constant development of DES includes adoption of new materials used for scaffold production, new design types, improved overexpansion abilities, new polymers coating and, finally, improved antiproliferative agents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…The third generation introduced ultrathin struts and advanced biodegradable polymer coating technology ( 63 65 ). Each progressive DES generation has witnessed an unceasing evolution of technology and design, all with the collective aspiration of achieving heightened long-term safety and efficacy ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The third generation introduced ultrathin struts and advanced biodegradable polymer coating technology ( 63 65 ). Each progressive DES generation has witnessed an unceasing evolution of technology and design, all with the collective aspiration of achieving heightened long-term safety and efficacy ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the use of BMSs, which do not contain antiproliferative drug layers, is associated with high restenosis rates. A breakthrough in coronary artery stent design was the development of DESs [ 55 ], which are now widely used due to their superior efficacy compared to BMSs. DESs are the preferred choice for percutaneous revascularization because the release of the drug from the polymer coating helps to reduce the risk of restenosis [ 56 ].…”
Section: Medical Devicesmentioning
confidence: 99%
“…However, its non-MRI compatibility and poor visibility in fluoroscopic images do not allow its in vivo placement [ 8 ]. Therefore, to improve the biocompatibility and hemocompatibility properties of stainless steel, coatings are commonly used to modify its surface features, reduce the surface free energy, smoothen the texture, neutralize the surface potential, and improve surface stability [ 8 , 15 ]. Furthermore, drugs can be added, and these modifications reduce thrombosis and neointimal proliferation, which reduces restenosis [ 16 , 17 ], and drug release controls intimal hyperplasia.…”
Section: Introductionmentioning
confidence: 99%